MEMPERKUAT SOLIDARITAS SOSIAL MELALUI PERAN KOMUNIKASI PERSUASIF DAN KUALITAS PELAYANAN: PSYCHOLOGICAL WELL BEING SEBAGAI MODERASI - Epsilandri Septyarini; Lusia Tria Hatmanti Hutami (Universitas Muhammadiyah Metro Lampung, 2021)
This study seeks to explain the aspects of social solidarity among members of a credit union which is strengthened by the influence of persuasive communication, service quality from its administrators as well as psychological well being variables that will moderate these two variables. The purpose of this study was to analyze the effect of persuasive communication, service quality on social solidarity of members in Credit Union Mitra Parahita, with the psychological well being variable as moderation. The research method used analysis of Structured Equation Modeling (SEM). Before the SEM analysis is carried out, the validity, reliability and fit models are first tested. This study used the accidental sampling method for members of the Mitra Parahita Gunung Kidul Credit Union. The results of this study indicate that Persuasive Communication does not have a significant effect on Social Solidarity. Service quality has a significant effect on Social Solidarity. Psychological Well-being does not moderate the effect of persuasive communication on social solidarity. Psychological Well-being does not moderate the effect of service quality on social solodarity. Psychological well-being has a significant effect on social solidarity.Keywords: Social Solidarity, Persuasive Communication, Service Quality, Psychological well being